Qualitative evaluation of destinations in the Arabic translation of Naguib Mahfouz's short stories based on Jean – Rene Ladmiral theory: ارزیابی کیّفی مقصدگرایی در ترجمه ى داستان‌های کوتاه نجیب محفوظ به زبان فارسى بر اساس نظریه ژان رنه لادمیرال (Journal of the College of Languages (JCL), 2024)
Evaluating translations and expressing their strengths and weaknesses can be a way forward for translators in this field and make the knowledge of translation more vibrant and dynamic. Since the purpose of translation is to better understand the text in the target language, the current research has analyzed the destinations of the translation of some of Naguib Mahfouz's short stories with the analytical-descriptive method and relying on the theoretical framework of Jean- Rene Ladmiral in order to determine its compatibility with the components This theory is valid. After examining and comparing the original text and the Persian translation, it was found that in the translation of these stories, the components of Admiral's theory such as displacement, legibility and heterogeneity have the highest frequency. Also, the translator has used the components of increase, disambiguation and deletion, which has tried to bring the original text closer to the destination and has provided a destination-oriented translation. Also, the components of minimal interpretation and the essence of translation were seen less in the translation. In some cases, he has turned to free translation of meanings and words, which has led to a translation far from difficulty and ambiguity in understanding the author's meaning.چکیدهارزیابی ترجمه‌ها و بیان نقاط قوت و ضعف آنها می‌تواند برای مترجمان در این عرصه راهگشا بوده و دانش ترجمه‌ را بالنده‌تر و پویاتر نماید. از آنجایی که هدف از ترجمه فهم بهتر متن در زبان مقصد است، پژوهش حاضر با روش تحلیلی-  توصیفی و با تکیه بر چارچوب نظری لادمیرال، مقصدگرایی ترجمه برخی از داستان‌های کوتاه نجیب محفوظ  را که توسط محمد رضا مرعشی پور به فارسی ترجمه شده است، مورد واکاوی قرار داده است تا میزان تطابق آن‌ را با مؤلفه‌های این نظریه بسنجد. پس از بررسی و تطابق متن اصلی و ترجمه فارسی، مشخص‌ گردید که در ترجمه این داستان‌ها، مؤلفه‌های نظریه لادمیرال نظیر جابه‌جایی، خوانایی و ناهمگون‌سازی بیشترین بسامد را دارا می‌باشند. همچنین مترجم از مؤلفه‌های افزایش، رفع ابهام و حذف نیز  بهره گرفته ‌که سعی بر نزدیک کردن متن اصلی به مقصد بوده و ترجمه مقصدمحوری ارائه داده است. همچنین مؤلفه‌های تفسیر حداقلی و چیستی ترجمانی کمتر در ترجمه دیده شد. وی در مواردی هم به ترجمه آزاد مدلول‌ها و واژگان روی آورده که این امر منجر به ترجمه‌ای دور از تکلف و ابهام در درک منظور نویسنده شده است.